(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
Industrial internships are a means for students to gain work experience while at the same time understanding the organizational environment and solving problems in the company/industry. This study aims to map the quality of soft skills and hard skills to the satisfaction of companies/industries where students carry out Industrial Internships, to get the results of mapping the quality of soft skills and hard skills the methods used are Importance-Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The object of research used in this study is the population of Industrial Internship students in 2021, amounting to 110 students. The questions used in the questionnaire use a range of 1-7 where the company/industry conducts an assessment by filling out a statement question questionnaire where the distance is 3 months, the distance is the ideal distance for stakeholders in assessing the quality of students’ soft skills and hard skills. The implication of the research results from the mapping of soft skills and hard skills of Industrial internships students is that the attributes contained in quadrant A consist of soft skills: self-confidence, motivation, and adaptability. And hard skills: Proficient in maintaining work tools, Learning Speed to use new work tools, and Ability to provide opinions, are attributes that need to be considered by the Department of Electronic Engineering to maintain company/industry trust to continue to accept the Industrial Internship program.